Association of Calcaneal Bone Marrow Lesions and Plantar Fascia Imaging Biomarkers With Chronic Plantar Heel Pain: A Case–Control Study. Issue 4 (17th November 2022) - Rogers, Jason; Jones, Graeme; Cook, Jill L.; Squibb, Kathryn; Halliday, Andrew; Wills, Karen; Lahham, Aroub; Winzenberg, Tania
Abstract : Objective: To determine associations between chronic plantar heel pain (CPHP) and imaging biomarkers derived from magnetic resonance imaging (MRI) and ultrasonography. Methods: We compared 218 participants with CPHP with 100 age‐ and sex‐matched population controls. We assessed imaging biomarkers on MRI (calcaneal bone marrow lesions [BMLs], plantar fascia [PF] signal and thickness, spurs, and fat pad signal) and B‐mode/power Doppler ultrasound (PF thickness, echogenicity, and vascularity). Covariate data collected included demographic characteristics, disease history, clinical measures, and physical activity by accelerometry. Data were analyzed using multivariable conditional logistic regression. Results: Plantar calcaneal BML size (mm 2, odds ratio [OR] 1.03 [95% confidence interval (95% CI) 1.02–1.05]), larger plantar spurs (OR for spurs >5 mm 2.15 [95% CI 1.13–4.10]), PF signal (OR for signal penetrating >50% of the dorsoplantar width 12.12 [95% CI 5.36–27.42]), PF thickness (mm, OR for MRI 3.23 [95% CI 2.36–4.43] and ultrasound OR 3.78 [95% CI 2.69–5.32]), and echogenicity (diffusely hypoechoic OR 7.89 [95% CI 4.02–15.48] and focally hypoechoic OR 24.92 [95% CI 9.60–64.69]) were independently associated with CPHP. PF vascularity was uncommon, occurring exclusively in cases (cases with signal n = 47 [22%]). Combining imaging biomarkers into 1 model, plantar BMLs and PF imaging biomarkers, but not fat pad signal or heel spurs, were independently associated with CPHP. Conclusion: Calcaneal BMLs and PF imaging biomarkers are associated with CPHP. Further research is required to understand whether these different markers represent distinct phenotypes of heel pain, and if so, whether there are specific treatment implications.